Field investigation of the heat stress in outdoor of healthcare workers wearing personal protective equipment in South China - Zhu, Yongcheng; Mao, Yudong; Li, Yanling; Tang, Tianwei; Jiang, Huilin; Qiao, Sicheng; Lin, Shaopeng; Zheng, Zhimin; Fang, Zhaosong; Chen, Xiaohui (Frontiers in Public Health, 2023)
Since the advent of coronavirus disease 2019 (COVID-19), healthcare workers (HCWs) wearing personal protective equipment (PPE) has become a common phenomenon. COVID-19 outbreaks overlap with heat waves, and healthcare workers must unfortunately wear PPE during hot weather and experience excessive heat stress. Healthcare workers are at risk of developing heat-related health problems during hot periods in South China. The investigation of thermal response to heat stress among HCWs when they do not wear PPE and when they finish work wearing PPE, and the impact of PPE use on HCWs’ physical health were conducted. The field survey were conducted in Guangzhou, including 11 districts. In this survey, HCWs were invited to answer a questionnaire about their heat perception in the thermal environment around them. Most HCWs experienced discomfort in their back, head, face, etc., and nearly 80% of HCWs experienced “profuse sweating.” Up to 96.81% of HCWs felt “hot” or “very hot.” The air temperature had a significant impact on thermal comfort. Healthcare workers’ whole thermal sensation and local thermal sensation were increased significantly by wearing PPE and their thermal sensation vote (TSV) tended towards “very hot.” The adaptive ability of the healthcare workers would decreased while wearing PPE. In addition, the accept range of the air temperature (Ta) were determined in this investigation. Graphical Abstract